Overhead power lines (MENA Report, 2013)
Development, qualification and supply of cables and associated accessories HTLS intended to equip the high voltage power lines. The cable called HTLS corresponds to the generic Aster 570. It is intended to replace a cable 570 mm2 AAAC.